Moxifloxacin-induced neutropenia in 26-year-old man - Kula Atik, Tuğba; Ispir, Emre; Aytekin, Aykut; Turhan, Ufuk; Yeniiz, Esma; Tas, Dilaver; Bedir, Orhan (The Journal of Infection in Developing Countries, 2018)
Moxifloxacin is a fourth generation widely used fluoroquinolone antibiotic. There are three cases of moxifloxacin-induced neutropenia reported in the literature and we report the fourth case. A 26-year-old man with pneumonia was treated with moxifloxacin because of penicillin allergy. On the second day of therapy, leukopenia [White blood cell (WBC) count 2.7×10³/μL] and neutropenia (neutrophils 1.21×10³/μL) occurred. Rothia mucilaginosa was isolated in sputum culture. On the fourth day of hospitalization moxifloxacin treatment was stopped and clarithromycin 500 mg PO twice daily was started. Leukopenia and neutropenia resolved one day after discontinuation of moxifloxacin that WBC and neutrophil count rose 4.5×10³/μL and 1.97×10³/μL, respectively. On the sixth day of hospitalization, WBC and neutrophil count was 4.3×10³/μL and 2.29×10³/μL, respectively. The immunomodulatory effects of moxifloxacin may result in the changes of WBC count like leukopenia with neutropenia. Moxifloxacin induced neutropenia may be more common and is an important adverse effect. More observational studies about safety profiles of moxifloxacin are needed.